PRINCIPLES OF WORKING WITH STUDENTS WHEN TEACHING PROBLEM SOLVING IN PRIMARY SCHOOL (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the need to change the methodology of teaching simple tasks in elementary school, which should include a practice-oriented approach, interdisciplinary communication and deep integration into modern society.